Reconstruction after gastrectomy and quality of life - Buhl, Klaus; Lehnert, Thomas; Schlag, Peter M.; Herfarth, Christian (World journal of surgery, 1995)
To evaluate quality of life and functional results following surgery for gastric cancer we studied 104 patients with no evidence of disease at a minimum of 12 months postoperatively. Patients were treated with total gastrectomy and jejunal pouch reconstruction according to Hunt-Lawrence-Rodino (n=59) or simple esophagojejunostomy (n=24) and distal subtotal gastrectomy (n=21). No significant differences were found between total gastrectomy with pouch reconstruction and distal gastric resection with respect to dumping or heartburn, whereas patients with total gastrectomy and restoration with esophagojejunostomy suffered from both. The latter group of patients also had reduced nutritional status. Although there is a lack of a proper definition of quality of life, all instruments applied to its measurement indicated improved results for patients with pouch reconstruction and those after distal gastrectomy, but we could not state any significant differences. We conclude that in terms of postoperative functional results as well as quality of life distal gastric resection has no advantage over total gastrectomy with pouch reconstruction; hence a reduction of surgical radicality in an attempt to improve postoperative results is not justified. Pouch reconstruction should be considered the treatment of choice for reconstruction after total gastrectomy.